Gestão de risco de compliance – principais entraves para as empresas brasileiras atingirem maior maturidade - Martins, Adriano de Oliveira (Universidade do Vale do Rio dos Sinos, 2018)
According to a Compliance Maturity research in Brazil, conducted by KPMG in 2016, companies generally have a low level of maturity in compliance risk management. Despite the importance of the topic, only 58% of companies claim to have compliance risk management mechanisms, while another 42% report not knowing them. Among the structures dedicated to the subject, 36% affirm that they do not have autonomy and independence to perform their functions, considered a governance good practice. Still, according to research, 52% do not have adequate resources. The Brazilian Institute of Corporate Governance (IBGC) understands risk as a possibility of 'something going wrong', but the current concept involves the quantification and qualification of uncertainty as 'losses' and 'gains' and the direction of planned events. The objective of this study is to identify the main obstacles that make the degree of maturity of the Brazilian companies in the subject of compliance to be low. For which, were interviewed in depth, some administration and supervisory advisers and, based on the available literature and the results of the recent research on risk maturity of compliance in Brazil, was possible to understand some of the main aspects that cause these companies to have this result. The results point mainly to: Belief that risks, especially compliance, will not materialize; Requirements related to the subject of compliance, do not apply in their companies; Reactive positioning regarding compliance with standards; Conflict of personal interests; Growing concern as well as the formation of directors in corporate governance in a reactive way; Lack of full knowledge of the responsibilities and impacts of being an advisor board; Increasing exposure to risks, resignation of positions in assemblies; Self-protection, breach of independence; Use of internal compliance structures, self-protection to meeting the needs of the main controller and attendance to conformities just to keep up appearances.
Keywords: Gestão de riscos de compliance; Papel do conselho de administração; Governança corporativa; Maturidade de risco de compliance; Efetividade do programa de compliance; Conflito de interesses; Compliance risk management; Board of directors role; Corporate governance; Maturity of compliance risk; Effectiveness of the compliance program; Conflicts of interest; ACCNPQ::Ciências Sociais Aplicadas::Administração